Bimbingan Belajar Literasi Dan Numerasi Bagi Anak Tingkat SD Dan SMP Di Desa Nagori Sihalpe Kec. Haranggaol Horison - Kammer Tuahman Sipayung; Novani Saragi; Santa Hoky Hutagalung; Desi Muliani Saragih; Rutmayana Br. Sianturi (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Community Service (PkM) Faculty of Teacher Training and Education (FKIP) HKBP Nomensen University Medan is a service program carried out by a team of students and DPL lecturers with the title "Literacy and Numeracy Tutoring for Elementary and Middle School Level Children in Nagori Sihalpe Village, District. Haranggaol Horizon”. Implementation of literacy and numeracy guidance is a fundamental competency that has an important role in determining the quality of a nation. In the field of education, especially at the elementary and junior high school levels, literacy and numeracy competencies are made the focus of learning and set as competency standards that students must have. Literacy and numeracy can provide provisions for students to adapt to life outside the classroom. However, in fact, the literacy and numeracy competencies of students in Indonesia are still low and education is also not as developed as it should be, so it is far behind other countries. Community Service (PkM) in Nagori village is carried out by providing tutoring activities to improve literacy and numeracy for elementary school and junior high school aged children in the area where students live.